TO LAMENT OR TO RESIST: REWRITING SARTRE’S TROJAN WOMEN ON THE TURKISH STAGE - Sağlam, Naciye (My University, 2025)
Jean-Paul Sartre’s adaptation of Euripides’ Trojan Women presents women’s suffering in the aftermath of war. In contemporary Turkish theatre, this classical text has been reinterpreted both through linguistic translation and performative acts that reframe the original work. Drawing on Morini’s (2022) assertion that “theatrical performance is itself a form of translation,” and applying Lefevere’s concept of rewriting to multimodal translation, this article examines two recent Turkish stage productions, Tatavla Theatre and Trabzon State Theatre, as examples of translational rewriting shaped by aesthetic choices. Through a qualitative comparative analysis of archival recordings, the study investigates how these productions recreates the source text through distinct performative strategies. While the Tatavla performance centers on collective grief and despair, employing minimalism and stillness, the Trabzon production brings resilience and agency into focus through dynamic movement and cinematic strategies. By comparing these approaches, the article demonstrates how translation becomes a site of gendered reinterpretation, one that goes beyond linguistic transfer, but actively shapes the visibility, voice, and bodily presence of women on stage.
Keywords: Performance translation; theatrical rewriting; Trojan Women; female agency